Remittance, Domestic Savings and Poverty Alleviation: Evidence from sub-Saharan Africa - Jallow, Momodou Lamin; Jiang, Hongli (International Journal of Economics and Financial Issues, 2025)
Remittances and domestic savings are crucial in economic progress, particularly in developing regions like Sub-Saharan Africa. However, the region is often characterised by low-income levels and inadequate savings, which hinder sustainable investment in growth-enhancing activities. To address this gap, international remittances have emerged as a significant source of external financing, complementing domestic savings. This research examines how remittance influences poverty alleviation in Saharan Africa through an extensive analysis of panels categorised by income and geographical criteria from 2004 to 2023. The outcomes from the two-way fixed effect model show that remittance has a significant positive effect on poverty alleviation. These findings remain robust even after employing robustness tests and implementing an instrumental variable approach to address potential endogeneity concerns. Further scrutiny of the underlying mechanism reveals that remittance stimulates domestic savings by enhancing individuals’ and households’ disposable income and access to funds. The empirical findings emphasise the need for improved governance and policy frameworks to optimise foreign capital utilisation and regional and international collaboration to harness the full potential of remittance to the region.